Komunikasi Interpersonal Guru dalam Memotivasi Belajar Siswa SMK Generasi Madani - Hidayat, Rafli Nur; Emeilia, Rindana Intan (CV. ITTC INDONESIA, 2024)
Student learning motivation is very important to achieve academic and non-academic achievements. This cannot be separated from how teachers are able to motivate students in learning, one of which is through interpersonal communication. This research aims to determine teacher interpersonal communication in motivating the learning of Generation Madani Vocational School students. Spitzberg and Cupach's theory of communication competence and Joseph A. DeVito's Interpersonal Communication Effectiveness were used to analyze this research. The research method used is descriptive qualitative. Data collection techniques used were interviews, observation and documentation. The results of the research show that the interpersonal communication carried out by teachers in motivating student learning at Generasi Madani Vocational School has gone well. This is demonstrated through aspects of openness, empathy, supportive attitude, positive attitude and equality. Interpersonal communication carried out by teachers also creates closeness and familiarity thereby motivating students' enthusiasm for learning. This research also shows that the teacher's communication competency theory consists of three components, namely motivation, knowledge and skills.